Suaeda salsa Polysaccharide Alleviates Hepatic Injury by Regulating Macrophage Polarization in a Mouse Model of High-fat Diet-induced Non-alcoholic Fatty Liver Disease - Sisi QIN; Changyu QIN; Yongheng WANG; Jiawen NING; Ziyu DONG; Lei WU; Xiaolong MA; Fuyuan CAO; Naijun WU; Xitong ZHANG; Liying HOU; Shuang LI (Shipin gongye ke-ji)
Objective: To investigate the regulation of macrophage polarization by Suaeda salsa polysaccharide (SSP) alleviates liver injury in a mouse model of high-fat diet (HFD)-induced non-alcoholic fatty liver disease (NAFLD) and the associated mechanisms involved. Methods: A model of NAFLD was established by feeding mice a HFD. Mice were randomly divided into control, model (HFD), low, medium, and high SSP intervention (100, 200, and 400 mg/kg SSP respectively), and atorvastatin (Ato). Except for the control group fed a standard maintenance diet, all other groups received a high-fat purified diet with 60% of energy derived from fat. The atorvastatin intervention group was administered a dose of 1 mg/kg daily via oral gavage, with continuous intervention maintained for 12 consecutive weeks. After 12 weeks, organ function indicators, peripheral blood and liver biochemical indices, and histopathological observations were performed. The mRNA and protein expression levels of macrophage polarization-associated genes in liver macrophages were determined using quantitative real-time polymerase chain reaction (qRT-PCR) and western blot assays, respectively, whereas the protein and mRNA expression levels of inflammation-associated factors were determined using ELISA and fluorescence qRT-PCR, respectively. Results: After 12 weeks of continuous intervention, compared with the group treated with HFD, the body weight and liver index of the mice inthe low-, medium-, and high-dose intervention groups of Suaeda salsa polysaccharides decreased extremely significantly (P<0.01), and the indices of other organs also decreased to varying degrees (P<0.01). The levels of total cholesterol, triglycerides, and low-density lipoprotein in serum and liver were significantly decreased (P<0.01), the level of high-density lipoprotein was significantly increased (P<0.01), and the levels of aspartate aminotransferase and alanine aminotransferase were significantly decreased (P<0.01). Histopathological analysis demonstrated reduced hepatic fat accumulation and hepatocellular steatosis in SSP-treated animals. The SSP-treated group exhibited significantly reduced protein expression levels of M1 macrophage markers inducible nitric oxide synthase (iNOS) and cluster of differentiation 86 (CD86) (P<0.01), while showing markedly increased expression of M2 macrophage markers cluster of differentiation 206 (CD206) and arginase-1 (Arg-1) (P<0.01) in hepatic tissues. Meanwhile, the transcriptional level of macrophage polarization markers detected by qRT-PCR was consistent with the trend of protein expression level detected by WB. Compared with the HFD group, the SSP intervention groups showed significantly lower TNF-α, IL-1β, and IL-6 (P<0.01) and significantly higher IL-10 levels in terms of both serum protein and hepatic mRNA expression (P<0.01). Conclusion: SSP can regulate the M1/M2 differentiation of hepatic macrophages, reduce injury secondary to HFD-induced hepatic fat accumulation, and alleviate the development of NAFLD, with the mechanism of action likely being associated with the regulation of macrophage polarization and expression of inflammatory factors.